Feasibility Analysis of Radec Learning Designs to Build Students’collaboration Skills In Determining pH Routes From Natural Indicators - Sari, Dini Intania; Wahyu, Wawan; Sopandi, Wahyu (Universitas Riau, 2022)
Student collaboration skills are one of the important things that can support 21st Century Skills. The purpose of this study is to develop students' collaboration skills in learning natural acid-base indicators using the appropriate learning model RADEC (Read, Answer, Discuss, Explain, Create). The research method used in this research is descriptive evaluative. This study involved 2 experts and 3 senior teachers to test the feasibility. A limited trial was given to 25 students from one of the State Senior High Schools (SMAN) in Rokan Hulu Regency, Riau Province. The instrument used is an internal due diligence sheet, an external feasibility test sheet, and an observation sheet on student collaboration skills. Data from the results of the feasibility test were scored, presented, tabulated, and categorized. Data from the results of observations and assessment reports are described and categorized. The results showed that the model RADEC was declared feasible based on internal, external, and feasibility tests TCOF. Students' collaboration skills are categorized as very good after learning through the model RADEC.